FACTORS FOR INCREASING LABOR PRODUCTIVITY IN THE NATIONAL ECONOMY - Ab (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, the national economy, intensive development of material production, rapid growth of output, especially net output relative to costs and population growth is the main way to solve the problems of national economy and economic development, the level of labor productivity. and its dynamics is influenced by many factors, as well as a number of ways by the Government and companies to increase labor productivity.